Spectropolarimetric study of the classical Cepheid η Aql: pulsation and magnetic field. Issue Volume 9:Issue S301(2013) (18th February 2014) - Butkovskaya, V.; Plachinda, S.; Baklanova, D.; Butkovskyi, V.
Abstract: We report the results of spectropolarimetric study of the classical Cepheid η Aql. We found that the longitudinal magnetic field of η Aql sinusoidally varies with the radial pulsation period, while the amplitude B, mean field B 0, and phases of maximum and minimum field change from year to year. We hypothesize that possible reasons of those variations are stellar axial rotation or dynamo mechanisms.